MEASURING THE FUTURE NEEDS OF ISLAMIC EDUCATION THROUGH THE ROLE OF ARTIFICIAL INTELLIGENCE - Karim, Abdul Rahim; Sugianto, Hendi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research aims to reveal the future needs of Islamic education through the role of Artificial Intelligence. The approach in this research uses a qualitative approach by utilizing literature review as a type of research that effectively facilitates the realization of the objectives of this research. The data collection stages are carried out systematically and structured through literature search studies that focus on the future needs of Islamic education through the role of Artificial Intelligence. Data analysis was carried out through modified analytical induction techniques in order to get a complete and structured picture so that the findings are accurate and avoid subjectivity bias. The results of this study can provide an understanding that there is a significant role of Artificial Intelligence in Islamic education in terms of teaching, learning, and administration as well as their respective impacts, there is a description of the educator paradigm in Islamic education through the the role of Artificial Intelligence which boils down to the certainty of educators in achieving the goals of Islamic education, and describes the paradigm of learners in Islamic education through the role of Artificial Intelligence which boils down to the model of learners as recipients, collaborators, and leaders.